A New Model of Green Purchase Intention and its Derivatives: Confirmatory Factor Analysis Validation of Constructs - Haruna, Victoria Masi (Information Management and Business Review, 2014)
There are various research frameworks found in the extant literature on green purchase intention. However, there is limited and fragmented comprehensive green purchase intention model in previous studies. Furthermore, the predictor variables and their constructs were diverse and were not tested in Nigeria. This study intends to confirm a comprehensive structural model of purchase intention and validating the constructs in Nigeria. The framework consists of five exogenous predictors (perceived green knowledge, government regulation, perceived value, and price sensitivity, green availability) and four endogenous (green purchase intention, perceived behavior control, environmental consciousness and green trust) Over-all, 76-items measure the variables adapted meticulously from various validated instruments. The questionnaires were distributed to 130 Nigerians in UUM. A return of 104 questionnaires was collected representing 80% response rate. Analysis methods using descriptive statistics, reliability, confirmatory factor analysis (CFA) in AMOS were conducted. The CFA of individual construct establishes adequate goodness fit of p-value >0.05 and GFI of more than 0.90. The Cronbach alpha also shows values above 0.80 indicating reliable constructs. The measurement model of exogenous and endogenous constructs achieves goodness of fit, indicating convergent validity. The CFA of exogenous constructs (p-value= 0.325, GFI= 0.903 and RMSEA=0.025) and endogenous constructs (p-value= 0.135, GFI= 0.914 and RMSEA=0.045) show adequate goodness of fit indices. This study is limited to the Nigerian students in UUM only; therefore a study with larger sample is suggested. It implies that this study could provide better understanding of the term â€œgreenâ€ among Nigerians. The study will be an impetus to upgrade government policy on green agenda and practitioners too will have insights on what marketing strategies to use in reaching out to potential consumers with green products. Previous studies lack holistic approach to green purchase intention model. The finding indicates that previous measurements could be adapted in Nigerian context.